Evaluating Environmental Contents in Comprehensive Passages in Junior Secondary School English Language Textbooks Used in Cross River State, Nigeria - B. Obi, Florence; Agbor, Comfort Nkongho; Onnoghen, Usang Nkanu; Etan, Michael Obun; Egbonyi, Darlington Egbe; Umoh, Suzanna Joseph; Akpan, Nsikan Anthony (Richtmann Publishing, 2021)
Serious concerns have been raised by many stakeholders in environmental issues including Cross River State Government, educationists, non-governmental organisations and even, the international funding agencies, about the quality and level of environmental information that can be accessed in both print and electronic media. This has become imperative because proper understanding of the origin of the present environmental challenges is the key to minimise the on-going abuses in future. This study was undertaken to investigate the level of environmental awareness issues contained in comprehensive passages present in English Language textbooks used by Junior Secondary School students in Cross River State, Nigeria. The study involves counting and analysing the number of passages dealing with environmental issues in 27 textbooks based on the four types of environments: abiotic, biotic, neutral and social. Two research questions were formulated and used to guide the study. Observed data were analysed using simple percentage technique. Results show that issues concerning the environment were reflected in all the textbooks but sometimes in an undesirable proportion. It was concluded that the practice of emphasising social and abiotic environments issues at the detriment of others do not auger well for proper development and impartation of environmental awareness to students. Received: 28 July 2021 / Accepted: 30 September 2021 / Published: 5 November 2021